Borrelia burgdorferi infection modifies protein content in saliva of Ixodes scapularis nymphs - Kim, Tae Kwon (BMC Genomics, 2021)
BACKGROUND: Lyme disease (LD) caused by Borrelia burgdorferi is the most prevalent tick-borne disease. There is evidence that vaccines based on tick proteins that promote tick transmission of B. burgdorferi could prevent LD. As Ixodes scapularis nymph tick bites are responsible for most LD cases, this study sought to identify nymph tick saliva proteins associated with B. burgdorferi transmission using LC-MS/MS. Tick saliva was collected using a non-invasive method of stimulating ticks (uninfected and infected: unfed, and every 12 h during feeding through 72 h, and fully-fed) to salivate into 2% pilocarpine-PBS for protein identification using LC-MS/MS. RESULTS: We identified a combined 747 tick saliva proteins of uninfected and B. burgdorferi infected ticks that were classified into 25 functional categories: housekeeping-like (48%), unknown function (18%), protease inhibitors (9%), immune-related (6%), proteases (8%), extracellular matrix (7%), and small categories that account for <5% each. Notably, B. burgdorferi infected ticks secreted high number of saliva proteins (n=645) than uninfected ticks (n=376). Counter-intuitively, antimicrobial peptides, which function to block bacterial infection at tick feeding site were suppressed 23-85 folds in B. burgdorferi infected ticks. Similar to glycolysis enzymes being enhanced in mammalian cells exposed to B. burgdorferi : eight of the 10-glycolysis pathway enzymes were secreted at high abundance by B. burgdorferi infected ticks. Of significance, rabbits exposed to B. burgdorferi infected ticks acquired potent immunity that caused 40-60% mortality of B. burgdorferi infected ticks during the second infestation compared to 15-28% for the uninfected. This might be explained by ELISA data that show that high expression levels of immunogenic proteins in B. burgdorferi infected ticks. CONCLUSION: Data here suggest that B. burgdorferi infection modified protein content in tick saliva to promote its survival at the tick feeding site. For instance, enzymes; copper/zinc superoxide dismutase that led to production of H(2)O(2) that is toxic to B. burgdorferi were suppressed, while, catalase and thioredoxin that neutralize H(2)O(2), and pyruvate kinase which yields pyruvate that protects Bb from H(2)O(2) killing were enhanced. We conclude data here is an important resource for discovery of effective antigens for a vaccine to prevent LD. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07429-0.